ENHANCING EDUCATIONAL COMIC BOOK INNOVATION THROUGH DESIGN THINKING: A CASE STUDY OF LAB BUDDY - Chairunnisa, Ainaya
The high number of demographic bonuses in Indonesia is a great advantage that needs to be optimized to achieve the vision of Indonesia Emas 2045, one of which is by improving the quality of education. Despite the government's efforts by increasing the quantity of schools, the quality of education in Indonesia still lags behind other countries. To overcome this problem, the Indonesian government must create a learning environment that can meet students' diverse learning needs and methods, especially in Mathematics. Technological advances have introduced a variety of innovative educational tools, one of which is mathematics educational comic. This research aims to develop product innovation of mathematics educational comic that suit the needs and preferences of students and parents using the concept of design thinking. Data collection was done by semi-structured interviews with the target customers of this product. This data was analyzed through open coding, pattern coding, and triangulation for validity. The findings show that the product has met the needs and preferences of the respondents, but still needs improvement in the sentence structure of the comic. The feedback provided should also be carefully considered before product implementation, highlighting the importance of design thinking in accurately meeting the needs and preferences of target customers.